Autothermal reforming of impure glycerol for H-2 production: Thermodynamic study including in situ CO2 and/or H-2 separation - M. A. Soria (2016)
In the present work, thermodynamics was applied to study the autothermal reforming (ATR) of impure glycerol (mixture of glycerol and methanol) to generate pure hydrogen. The equilibrium compositions were calculated using the Gibbs free energy minimization method and simulations were performed in a wide range of conditions of pressure (1-20 atm), temperature (600-1000 K), oxygen to glycerol feed molar ratio (0.0-3.0), and water to glycerol feed molar ratio (3-12). The effect of in situ CO2 and/or H-2 removal was investigated as well, in the perspective of reaction/separation process integration in a hybrid multifunctional reactor. Whatever the composition of the glycerol fed, the in situ separation of H-2 and CO2 in ATR process maximizes the hydrogen yield and completely eliminates methane, carbon monoxide and carbon dioxide formation. At 700 K, it is possible to improve the H-2 yield, with respect to the traditional reactor, up to 186% when CO2 removal is considered, up to 152% when only H-2 removal is implemented, and by 195% when both H-2 and CO2 removal are considered in the hybrid reactor. From the investigation of the energetically neutral conditions, it was found that in the sorption-enhanced process, with or without in situ H-2 separation, no partial oxidation reactions are needed to provide the required heat to maintain the isothermal reformer at the desired temperature, and consequently the yield of hydrogen can be improved up to 6.93, which is close to the stoichiometric theoretical value of 7. Copyright (c) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.